Curbing the Growth of Wax Bean (Vigna unguiculata L.) via a Novel Complex of Nano Zinc Oxide/Vermicompost - Farideh BEHBOUDI; Iraj ALLAHDAAI; Ebrahim Mohammadi GOLTAPEH; Ali Mohammad Modares SANAVI; Marjan Najafi DISFANI (Notulae Scientia Biologicae, 2016)
Vermicompost (VC) samples were prepared from manure and spent mushroom compost (SMC) and were impregnated with zinc oxide nanoparticles (ZnO NPs), giving ZnO NPs/VC complexes that were added into the soil in which wax beans (Vigna unguiculata L.) were then planted. The study was carried out through a factorial experiment in a randomized complete block design with three factors. The experimental factors included: ZnO NPs (0, 0.4, 0.8 and 1.2 mg kg-1), two substrate types (cow manure and SMC) and VC (2.5, 5 and 7.5 weight percentages). To the substrate types, adult earthworms (Eisenia fetida) were added. Specifically, after three months, the prepared VC was soaked in ZnO NPs solutions, mixed with soil (according to cultivation substrate weight), then employed in wet plantation of wax beans. The obtained results showed that with increasing ZnO NPs, leaves’ chlorophyll, grains number per pod, stem length, hundred grains weight, grain yield, and the grain protein content significantly decreased. In general, the usage of these NPs in the applied amounts could curb the undesired growth of this species.